Fishermen Social Movements in West Sumatra: Issues, Actors, and Tactics of the Movement - Hapsari, Dwi Retno; Kinseng, Rilus A; Sarwoprasodjo, Sarwititi; Putri Simanjuntak, Asnika; Anam, Khairil; Sarifuddin, Andri; Sulistiyowati, Iin (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2020)
The objectives of this study are to examine the main issue that provoke social movement of fishermen in West Sumatra, to identify the related actors, and to analyze the advocacy strategy carried out by fishermen. This research was conducted in July 2019 and took place in two locations, namely the City of Padang and West Pasaman Regency. The study used qualitative approach. From this study, it is revealed that the main issue that provoke social movements in West Sumatra was the issue of Regulation No. 71 of 2016 by the Minister of Maritime Affairs and Fisheries related to the prohibition of certain fishing gear. This regulation prohibits the use of 4 mm mesh size of the net and the use of lamps in operating the liftnet which reaches up to 25-30 thousand watts of power. This regulation has created a huge burden to fisherman’s work. The Other issue that is also triggering the movement was the arrestment of 6 fishing boats on June 11, 2016. Meanwhile, the main actors who are directly related to this movement are fishermen who are using liftnet (bagan). These actors can be divided into two main categories, namely movers and